The Study of The Validity of The Surface Structure of Holy Quran - Esmaeil Rezaei (AHKAM : Jurnal Ilmu Syariah, 2019)
The validity of the surface structure of the Holy Qur'an is one of the most important Qur'anic debates, which also affects the issues of Islamic law. The meaning of surface structure of the Qur'an is that the surface structure of the Qur'an is understandable to every reader and listener, as well as any human text, and that which man understands the surface structure of the Qur'an by means of verbal and illogical indications. The current paper examines the validity of the surface structure of the Holy Quran, following expanding the conceptual subject of the research.  Given the thematic documents presented, this is a descriptive-analytical paper with library sources data collection tool. The findings indicate that: The most important reason for believing in the validity of the Holy Qur'an surface structure is that this holy scripture includes the plan of human happiness in the world and the Hereafter. Therefore, if the surface structure of the Holy Quran is not justified, how one can use its surface structure to answer difficult questions that limited human reason is incapable of answering. In addition, the Holy Qur'an, although revelation and has been revealed by God, but because it is revealed in the form of words, it is governed by the principles and rules governing all languages, among which are the validity of their surface structure for those familiar with the language. Keabsahan struktur permukaan Al-Qur'an adalah salah satu perdebatan Al-Qur'an yang paling penting karena  mempengaruhi masalah hukum Islam. Makna struktur permukaan Al-Qur'an adalah bahwa struktur permukaan Al-Qur'an dapat dipahami oleh setiap pembaca dan pendengar, serta teks manusia mana pun, dan apa yang dipahami manusia oleh struktur permukaan Al-Qur'an dengan cara indikasi verbal dan tidak logis. Penelitian ini  meneliti validitas struktur permukaan Al-Qur'an, dengan memperluas subjek konseptual penelitian. Mengingat dokumen tematik yang disajikan, pendekatan deskriptif-analitis dengan alat pengumpulan data sumber perpustakaan. Temuan menunjukkan bahwa: alasan paling penting untuk percaya pada validitas struktur permukaan Al-Qur'an adalah bahwa kitab suci ini mencakup rencana kebahagiaan manusia di dunia dan akhirat. Karena itu, jika struktur permukaan Al-Qur'an tidak benar, bagaimana seseorang dapat menggunakan struktur permukaannya untuk menjawab pertanyaan-pertanyaan sulit yang membatasi akal manusia. Selain itu, Alquran, meskipun wahyu dari Allah,  tetapi karena diturunkan dalam bentuk kata-kata, diatur oleh prinsip dan aturan yang mengatur semua bahasa, di antaranya adalah validitas struktur permukaan untuk mereka yang terbiasa dengan bahasa.